2019
DOI: 10.1109/access.2019.2893624
|View full text |Cite
|
Sign up to set email alerts
|

Matrix Differential Decomposition-Based Anomaly Detection and Localization in NFV Networks

Abstract: Network function virtualization (NFV) is a promising network paradigm that enables the design and implementation of novel network services with lower cost, increased agility, and faster time-to-value. However, network anomalies caused by software malfunction, hardware failure, mis-configuration, or cyber attacks can greatly degrade the performance of NFV networks. A few matrix decomposition-based methods have shown their effectiveness in finding the existence of network-wide anomalies. However, a little attent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Chen, Jing, et al [72] proposed the matrix differential decomposition (MDD) method of anomaly identification in the NFV network. They designed a technique that works in three phases.…”
Section: Matrix Differential Decompositionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chen, Jing, et al [72] proposed the matrix differential decomposition (MDD) method of anomaly identification in the NFV network. They designed a technique that works in three phases.…”
Section: Matrix Differential Decompositionmentioning
confidence: 99%
“…Their approach used VM data for anomaly detection. The method proposed by Jing Chen [72] is a matrix decomposition method, in which they use a three-step procedure to detect the anomaly and solve the device localization problem that generates the anomaly. This method not only gives good results but also reduces the presence of anomalies in the NFV network through the localization of devices.…”
Section: Comparative Analysis Of State-of-the-art Anomaly Detection I...mentioning
confidence: 99%
“…With this approach, the solution presented here provides the TM between all possible combinations of OD pairs traversing S1 or S2. The getPorts( β 0 , β 1 ): linkports [2] function (lines 41-52) returns the β 0 , β 1 link ports. If the β 0 , β 1 link is an element of the L 1 , the function returns only the switch port (lines [43][44][45].…”
Section: ) Generate Lp Set Algorithmmentioning
confidence: 99%
“…A traffic matrix (TM) provides the traffic throughput between any OD pairs in a network over a specific time interval [1,2]. This information is essential for several activities in traffic engineering [42] (TE) such as switch load balancing, traffic analysis, and fault tolerance analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Existing researches [6], [7], [8] have shown that the abnormal behaviors of VMs usually come with a significant change in resource metrics, so it is a good way to implement anomaly detection for VMs by collecting and analyzing its multi-dimensional resource metrics data. Although there have been many interesting researches for anomaly detection, including statistical and probability methods [9], [10], distance-based methods [11], [12], domain-based methods [13], [14], reconstruction-based methods [15], [16], [17], and information theory based methods [18], as classified in [19], detecting anomalies of VMs in virtualized network slicing environment still faces many challenges:…”
Section: Introductionmentioning
confidence: 99%